Design of Wind Power Generator for Tambak Houses - Marhatang Marhatang; Herman Nawir; Muhammad Ruswandi Djalal; Maudini Maudini; Muh Amar Syarifuddin (Journal of Electrical Technology UMY, 2023)
Wind Power Generation (WPG) requires specific wind conditions to generate electrical energy. Indonesia's wind potential enables the development of small-scale power plants. Innovations in windmill technology need to be developed to ensure maximum results in low wind speed conditions. This research proposes the design and implementation of WPG using a vertical axis to provide lighting for pond houses. The goal is to benefit pond workers in coastal areas that lack electricity from the National Electric Company. The manufacturing stages include design and testing. Based on the design results, the dimensions of the propeller area are 0.393m, the frame height is 1.5m, and the wind turbine height is 0.75m. The performance test of the WPG yielded the highest turbine power value at 15.30 WITA, with a turbine power output of 25.38 Watts.